2006
DOI: 10.1002/cne.20930
|View full text |Cite
|
Sign up to set email alerts
|

Multiple olfactory receptor neurons and their axonal projections in the antennal lobe of the honeybee Apis mellifera

Abstract: The poreplate sensilla of honeybees are equipped with multiple olfactory receptor neurons (ORNs), which innervate glomeruli of the antennal lobe (AL). We investigated the axonal projection pattern in glomeruli of the AL (glomerular pattern), formed by the multiple ORNs of individual poreplate sensilla. We used the different glomerular patterns to draw conclusions about the equipment of poreplate sensilla with different ORN types. ORNs of single poreplate sensilla were stained and analyzed by laser-scanning con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 58 publications
2
61
0
Order By: Relevance
“…For another hymenopteran species, the honeybee, it has been shown that each glomerulus is innervated by a single ORN type, and the spatial position of glomeruli is species specific and conserved across individuals (Galizia et al, 1998(Galizia et al, , 1999Kelber et al, 2006). We selected a number of glomeruli within the region of the AL where the MG is located in large workers.…”
Section: Al Phenotypesmentioning
confidence: 99%
“…For another hymenopteran species, the honeybee, it has been shown that each glomerulus is innervated by a single ORN type, and the spatial position of glomeruli is species specific and conserved across individuals (Galizia et al, 1998(Galizia et al, , 1999Kelber et al, 2006). We selected a number of glomeruli within the region of the AL where the MG is located in large workers.…”
Section: Al Phenotypesmentioning
confidence: 99%
“…In honeybees, ORNs are mainly located in sensilla placodea. These sensilla contain up to 30 ORNs that innervate the AL with highly diverse glomerular patterns (Kelber et al, 2006), thus maximizing the chance that two arbitrary odors may activate two ORNs within the same sensillum. The ORNs that respond to the leading odor could suppress the ORN responses to the trailing odor in the same sensillum.…”
Section: Asynchronous Mixtures Contain Information About Their Componmentioning
confidence: 99%
“…Individual olfactory sensilla on the antennae are generally equipped with a high number of ORNs [Schneider and Steinbrecht, 1968;Esslen and Kaissling, 1976;Kelber et al, 2006] compared, for example, to moths or flies that have only one to three receptor neurons in a single sensillum. The advantages of multiple ORNs are not yet clear.…”
mentioning
confidence: 99%